Performance Evaluation of Time and Cost In The Bungur-Kedoyo Tulungagung Road Construction Project Using The Earned Value Method - Bahrudin, M. Sulton; Patriadi, Andi; Sajiyo, Sajiyo (Devotion : Journal of Research and Community Service, 2025)
Road infrastructure is essential for supporting transportation, fostering economic growth, and enhancing community mobility. However, the Bungur-Kedoyo road construction project in Tulungagung has faced challenges in time and cost management, impacting overall project performance. This study aims to evaluate the project's time and cost performance using the Earned Value Method (EVM), a robust tool that compares planned work, completed work, and actual costs to provide a comprehensive performance analysis. Data from the 25th-week project report revealed delays, with a Schedule Variance (SV) of -Rp. 315,481,514.90 and a Schedule Performance Index (SPI) of 0.970, indicating slower progress than initially planned (SPI < 1). These results highlight the need for improved project scheduling and enhanced control mechanisms to mitigate delays and manage costs effectively. By identifying inefficiencies and areas requiring intervention, the study provides actionable recommendations for improving project management practices. It concludes that integrating EVM into time and cost control processes can significantly enhance project efficiency and reliability. This research contributes to advancing infrastructure development by offering insights that can be applied to similar projects, ensuring timely and cost-effective delivery while promoting sustainable growth in the road construction sector.